Izi = išātu, Ká-gal = abullu and Níg-ga = makkūru - Civil, M. (1971)
A Reconstruction of Sumerian and Akkadian Lexical Lists prepared by В. Landsberger; Edited by Miguel Civil, with the collaboration of Hans G. Güterbock, William W. Hallo, Harry A. Hoffner, Erica Reiner.